Understanding the Characteristics of 1996 Extreme Rainfall and Its Association with a Megalandslide in Podi Watershed, Central Sulawesi, Indonesia - Djuraini, Moh. Fahry (Journal of Climate Change Society, 2025)
The 1996 Podi megalandslide in Central Sulawesi, Indonesia, occurred in a remote tropical watershed with limited data, causing severe geomorphic disturbance. Using Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) and post-event Landsat 5 imagery, this study reconstructs the hydrometeorological sequence preceding the event. Rainfall extreme indices from ETCCDI were analyzed to examine intensity, duration, and temporal distribution. Results reveal that September 1996 experienced prolonged dryness (Rx5day: 65 mm; Rx1day: 35–40 mm), which likely desiccated soils and reduced root–soil cohesion in the limestone–ophiolite terrain. In early October, rainfall intensified sharply (Rx5day: 216 mm; Rx1day: 113 mm), persisting until mid-November. The temporal overlap of antecedent dryness, intense rainfall, and fragile geology indicates a compound triggering mechanism. This study highlights how rainfall extremes contributed to slope failure in tropical montane watersheds and emphasizes the need for early warning frameworks integrating satellite-based rainfall and geological susceptibility in remote data-scarce regions.